Evaluacion de tres abonos organicos con tres dosis en la Asociacion de cultivos de vicia (vicia sativa l.) y avena (avena sativa l.) en el sector salache, cantón latacunga, provincia de cotopaxi 2021-2022. - Martínez Tocagon, Wilmer Eduardo (2022)
In this research study, the association of Vicia (Vicia sativa L.) and Oats (Avena sativa L.) was analyzed and studied in its development found in an eroded soil, so a randomized complete block design ( D.B.C.A), with 10 treatments and three repetitions, giving a total of 30 experimental units, the research was carried out in a plot of 4 meters wide by 2.5 long, giving an area of ten square meters for each experimental unit, which were developed with three organic fertilizers, Eco Fertilizer, Worm Humus, and Guinea Pig Fertilizer, in doses of 20 t/ha, 30 t/ha, 40 t/ha. The results obtained for the variable of the number of plants in the association of Vicia (Vicia sativa L.) and Oats (Avena sativa L.) were 791 plants, in the variable of plant height an average of 58 cm was obtained, in the variable of biomass an average weight of 3.52 kg was obtained, in the variable of green matter an average weight of 899 gr was obtained and in the variable of dry matter, an average weight of 657 gr was obtained. The results of the research study also revealed that treatment 9, which is the organic guinea pig manure with a high dose of 40 t/ha, is the best in terms of the development of the association of Vicia (Vicia sativa L.) and Oats (Avena sativa L.) and the control is the one that had the least development compared to the other treatments. In the soil analysis carried out, it was found that the application of organic fertilizers (eco fertilizer, vermicompost, guinea pig fertilizer) at doses; 20 t/ha, 30 t/ha, 40 t/ha considerably increased soil nutrients, nitrogen by an average of 5% increased to 15%, the phosphorus at the beginning had 8.09% increased to 32%, the potassium at the beginning had 3.08% increased to 3.20% and the micronutrients in the soil were increased and the pH of the soil decreased from 10.40 to 9.45.